2018
DOI: 10.5116/ijme.5b07.d108
|View full text |Cite
|
Sign up to set email alerts
|

What factors motivate junior doctors to engage as clinical tutors? A qualitative study

Abstract: ObjectivesThe study aimed to explore and identify factors motivating junior doctors to engage as long-term clinical tutors in undergraduate medical education. MethodsIn this qualitative study, twenty-seven participants were recruited among junior doctors attending preparatory tutor courses at the Sahlgrenska Academy, University of Gothenburg, and the Primary Healthcare system, West Sweden. They were asked to respond to open-ended questions and write a short account of their needs as clinical tutors for medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The foundation doctors identified several challenges to their teaching through both the questionnaire and FGDs. As found by previous studies (Below et al, 2018;Gill et al, 2008;Qureshi et al, 2013) the most common obstacle discussed by the doctors was lacking time to teach. As the need for service provision increases due to the added pressures felt throughout the NHS, the time available for training reduces.…”
Section: Discussionmentioning
confidence: 71%
“…The foundation doctors identified several challenges to their teaching through both the questionnaire and FGDs. As found by previous studies (Below et al, 2018;Gill et al, 2008;Qureshi et al, 2013) the most common obstacle discussed by the doctors was lacking time to teach. As the need for service provision increases due to the added pressures felt throughout the NHS, the time available for training reduces.…”
Section: Discussionmentioning
confidence: 71%
“…Research has shown that clinical supervision offers little merit value, short of time and space, and limited financial compensation (von Below et al 2018). Likewise, neither the career nor the extra income provided by supervision towards the end of their professional life cycles seems to be a driving force when the physicians reflect on their reasons for choosing supervision.…”
Section: Resultsmentioning
confidence: 99%
“…The challenge to adapt the clinical workplace, primarily focused on providing safe healthcare, to accommodate clinical supervision is well known [33,[48][49][50]. Lack of time to teach is frequently seen as a barrier to effective clinical supervision [19,33,34,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%